2021
DOI: 10.2196/26096
|View full text |Cite
|
Sign up to set email alerts
|

Using Biometric Sensor Data to Monitor Cancer Patients During Radiotherapy: Protocol for the OncoWatch Feasibility Study

Abstract: Background Patients with head and neck cancer (HNC) experience severe side effects during radiotherapy (RT). Ongoing technological advances in wearable biometric sensors allow for the collection of objective data (eg, physical activity and heart rate), which might, in the future, help detect and counter side effects before they become severe. A smartwatch such as the Apple Watch allows for objective data monitoring outside the hospital with minimal effort from the patient. To determine whether such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Before initiating the current study, a study protocol was published in a peer-reviewed journal [18]. The adherence rate (wear time >12/h/d during the study period) of 31% was lower than we had anticipated.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Before initiating the current study, a study protocol was published in a peer-reviewed journal [18]. The adherence rate (wear time >12/h/d during the study period) of 31% was lower than we had anticipated.…”
Section: Discussionmentioning
confidence: 91%
“…In the OncoWatch 1.0 study, we established a framework for testing a smartwatch for home monitoring in a public healthcare hospital. In this study, we could not obtain the adherence rate to the smartwatch predefined in the study protocol [18]. Nevertheless, we gained novel knowledge on using smartwatches for collecting objective data in a patient group with HNC that is underrepresented in the studies of [10,20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A power calculation is not required for this type of study because it is a feasibility study with no control group and no formal statistical hypothesis testing, and thus, the sample size is not driven by formal power calculations. This sample size corresponds to studies of the same nature in the literature [ 26 - 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…To reflect the present Danish experience with the feasibility of wearable sensors in oncology, a literature search was performed. Searching the scientific database PubMed using the search term: 'cancer and wearable sensor and Denmark and feasibility' revealed only two studies [48][49][50](case 1 (protocol [48] and result article [49]) and 2 (protocol article [50])) and a review on the topic performed by our research group [31]; the same two studies were identified when searching ClinicalTrials.gov using the same search term. Case 3 is a study designed by the author group but not yet performed.…”
Section: Case Presentationsmentioning
confidence: 99%